New Indonesian Science Curriculum for Junior High School: A Content Analysis to Support STEM SDGs - Greny Mispi Anisa Sari; Vika Yulinda Antika; Remanda Arya Wisutama; Laela Nisfi Syiami; Nurul Fitriyah Sulaeman; Atin Nuryadin; Lambang Subagiyo (Jurnal Literasi Pendidikan Fisika (JLPF), 2022)
Recently, Indonesia has experienced changes in the school curriculum to be more in line with the development of globalization. The 2013 curriculum changed into the "Merdeka" curriculum in 2021. However, as the curriculum changes, there is still very little research on the relation of the new curriculum with Sustainable Development Goals (SDGs) and the learning approach to achieve these goals such as STEM learning. The method used in this research is content analysis. From the results, it appears that the engineering side of the new curriculum is more visible through kata kuncis in learning outcomes such as observing, questioning, predicting, planning, conducting investigations, processing, analyzing data, informing, reflecting, and communicating results. However, the relation new curriculum is still relatively low on the SDGs issue, which can be seen in several material aspects such as efforts to prevent and overcome pollution, climate change, and environmental conservation. Therefore, STEM SDGs learning must be further improved in order to prepare students for the future life.